1988
DOI: 10.1073/pnas.85.9.3175
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of carnosine, homocarnosine, and anserine present in muscle and brain.

Abstract: Carnosine, homocarnosine, and anserine are present in high concentrations in the muscle and brain of many animals and humans. However, their exact function is not clear. The antioxidant activity of these compounds has been examined by testing their peroxyl radical-trapping ability at physiological concentrations. Carnosine, homocarnosine, anserine, and other histidine derivatives all showed antioxidant activity. All of these compounds showing peroxyl radicaltrapping activity were also electrochemically active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
439
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 691 publications
(472 citation statements)
references
References 30 publications
11
439
0
6
Order By: Relevance
“…In our opinion, the hypothetical role(s) of carnosine-related dipeptides could be linked to some common feature(s) concerning the metabolism of these cell populations, although no direct evidence in this direction is at present available. Nevertheless, there is strong evidence that carnosine and structurally related dipeptides possess a wide range of properties, such as antioxidant, metal chelator, free radical scavenger, inhibitor of protein glycosilation (Boldyrev et al, , 1988(Boldyrev et al, , 1997Kohen et al, 1988;Boldyrev, 1993;Hipkiss et al, 1995;Preston et al, 1998; for review, see Hipkiss, 1998), which enable them to prevent several types of damage responsible for cell senescence (McFarland and Holliday, 1994;Sri-Kantha et al, 1996). Thus, carnosine-related dipeptides could exert a protective role in cell populations of the nervous system which, due to their location and/or function and metabolism, can come in contact with potentially harmful substances.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our opinion, the hypothetical role(s) of carnosine-related dipeptides could be linked to some common feature(s) concerning the metabolism of these cell populations, although no direct evidence in this direction is at present available. Nevertheless, there is strong evidence that carnosine and structurally related dipeptides possess a wide range of properties, such as antioxidant, metal chelator, free radical scavenger, inhibitor of protein glycosilation (Boldyrev et al, , 1988(Boldyrev et al, , 1997Kohen et al, 1988;Boldyrev, 1993;Hipkiss et al, 1995;Preston et al, 1998; for review, see Hipkiss, 1998), which enable them to prevent several types of damage responsible for cell senescence (McFarland and Holliday, 1994;Sri-Kantha et al, 1996). Thus, carnosine-related dipeptides could exert a protective role in cell populations of the nervous system which, due to their location and/or function and metabolism, can come in contact with potentially harmful substances.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, neurons contain very low levels of reduced glutathione, an antioxidant responsible for removal of cytosolic peroxides (Slivka et al, 1987), and their membranes contain a high proportion of freeradical-susceptible polyunsaturated fatty acids (see Evans, 1993). Interestingly enough, several studies demonstrated a significative antioxidant activity for carnosine-related dipeptides, both in muscle and brain tissue (see for example Boldyrev et al, 1987Boldyrev et al, , 1988Boldyrev et al, , 1997Kohen et al, 1988;Boldyrev, 1993). The activity showed by these dipeptides is due to the imidazole moiety of the molecule, and consists of several anti-oxidant properties, i.e.…”
Section: Antioxidant Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] The endogenous dipeptide L-carnosine (β-alanyl-L-histidine) was discovered by Gulewitsch and Amiradzibi [25] from muscle tissue extracts in 1900 [26,27] and is found in several organs including the brain (olfactory bulb and hippocampus) [28], cardiac muscle, kidney and stomach. [29,30] In the skeletal muscle and nerve cells it is found at concentrations of up to 20 mM.…”
Section: Introductionmentioning
confidence: 99%
“…An involvement in neurotransmission within the olfactory system has been proposed in the past [23]. Nevertheless, the distribution of carnosine-LI in the central nervous system (CNS), prevalently associated to glial/ependymal cells [3,7,26] along with the identification of several effects displayed by these molecules in vitro [4,5,13,18,24], strongly suggest that they could subserve other functions [7]. In the mammalian brain, carnosine has been detected almost exclusively in astrocytes, oligodendrocytes, ependymal cells and tanycytes [3,10,26; for review see Ref.…”
Section: Introductionmentioning
confidence: 99%